2019
DOI: 10.1002/kjm2.12065
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of the suppressed NF‐κB/TLR4 signaling pathway on oxidative stress of lung tissue in rat with acute lung injury

Abstract: The pathogenesis of acute lung injury (ALI) is characterized by lung inflammation and lung oxidative stress. The study was conducted in order to investigate the effect toll‐like receptor 4 (TLR4) and nuclear factor‐kappa B (NF‐κB) exhibited on oxidative stress in ALI. After the rats had been assigned into different groups, arterial blood, white blood cell (WBC), lung permeability index (LPI), wet/dry (W/D) ratio, TLR4 and NF‐κB expression and superoxide dismutase (SOD), myeloperoxidase (MPO), malondialdehyde (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 41 publications
2
16
0
1
Order By: Relevance
“…NF- κ B is an important transcription factor ubiquitous in the central nervous system and a key transcription factor involved in oxidative stress and the inflammatory response [ 45 ]. The NF- κ B signaling pathway is involved in inhibition of oxidative stress-induced cell damage [ 46 ]. p65 and I- κ B α have been identified as indicators for detection of the NF- κ B signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…NF- κ B is an important transcription factor ubiquitous in the central nervous system and a key transcription factor involved in oxidative stress and the inflammatory response [ 45 ]. The NF- κ B signaling pathway is involved in inhibition of oxidative stress-induced cell damage [ 46 ]. p65 and I- κ B α have been identified as indicators for detection of the NF- κ B signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The destruction of the intestinal flora causes bacterial translocation, activates the lung immune response, induces the production of a large number of inflammatory factors, triggers oxidative stress, and subsequently damages the lung tissue. 70 FMT may reduce the oxidative damage and enhance the antioxidant capacity. Therefore, the imbalance of the intestinal flora increases the immune response to the bacteria in the lungs through the gut-lung axis and activates the oxidative stress in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the NF-κB pathway is critical for the induction of inflammatory response and oxidative stress. Additionally, the early studies showed that the blockade of TLR4/NF-κB pathway effectively inhibited oxidative stress and inflammatory responses in the lungs (Deng et al 2017 ; Zhang et al 2019 ). Therefore, the HMGB1/TLR4/NF-κB pathway is an important pathway to induce inflammatory response and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%